Breakthrough : the story of James O. Fraser and the Lisu people - Haron, Ken; Simpson, Stuart; Pearson-Miles, Patrick; Crossman, Eileen; OMF International (Worcester, PA : Gateway Films, 2008)
An inspiring half-hour docudrama about a man, his journey, and a people changed through prayer. A story about personal sacrifice, perseverance, and more.
An inspiring half-hour docudrama about a man, his journey, and a people changed through prayer. A story about personal sacrifice, perseverance, and more.
Keywords: Fraser, James Outram,1886-1938 -- Drama; Missionaries Biography -- China -- Biography -- Drama; Missionaries -- Great Britain -- Biography -- Drama